PcMuORP1, an Oxathiapiprolin-Resistance Gene, Functions as a Novel Selection Marker for Phytophthora Transformation and CRISPR/Cas9 Mediated Genome Editing - Wang, Weizhen; Xue, Zhaolin; Miao, Jianqiang; Cai, Meng; Zhang, Can; Li, Tengjiao; Zhang, Borui; Tyler, Brett M.; Liu, Xili (Frontiers in Microbiology, 2019)
Phytophthora, a genus of oomycetes, contains many devastating plant pathogens, which cause substantial economic losses worldwide. Recently, CRISPR/Cas9-based genome editing tool was introduced into Phytophthora to delineate the functionality of individual genes. The available selection markers for Phytophthora transformation, however, are limited, which can restrain transgenic manipulation in some cases. We hypothesized that PcMuORP1, an endogenous fungicide resistance gene from P. capsici that confers resistance to the fungicide oxathiapiprolin via an altered target site in the ORP1 protein, could be used as an alternative marker. To test this hypothesis, the gene PcMuORP1 was introduced into the CRISPR/Cas9 system and complementation of a deleted gene in P. capsici was achieved using it as a selection marker. All of the oxathiapiprolin-resistant transformants were confirmed to contain the marker gene, indicating that the positive screening rate was 100%. The novel selection marker could also be used in other representative Phytophthora species including P. sojae and P. litchii, also with 100% positive screening rate. Furthermore, comparative studies indicated that use of PcMuORP1 resulted in a much higher efficiency of screening compared to the conventional selection marker NPT II, especially in P. capsici. Successive subculture and asexual reproduction in the absence of selective pressure were found to result in the loss of the selection marker from the transformants, which indicates that the PcMuORP1 gene would have little long term influence on the fitness of transformants and could be reused as the selection marker in subsequent projects. Thus, we have created an alternative selection marker for Phytophthora transformation by using a fungicide resistance gene, which would accelerate functional studies of genes in these species.